Sosialisasi Pengenalan dan Penanganan Limbah Bahan Berbahaya Beracun (B3) Rumah Tangga Di RT 014 Kelurahan Bagan Pete Kota Jambi - Fitria Eka Putri; Andy Amir; Fajrina Hidayati (Jurnal Salam Sehat Masyarakat (JSSM), 2022)
Hazardous and toxic materials (B3) are substances, energy, and/or other components which due to their nature, concentration and/or amount, either directly or indirectly, can pollute and/or damage the environment, and/or endanger the environment. health, and the survival of humans and other living things. Hazardous waste affects health by harming humans directly (due to explosions, fires, reactive, corrosive) or indirectly (acute toxic and krosis). The capacity for handling waste, especially B3 waste, carried out by the community and local governments is not yet optimal. Waste that is not managed properly will affect the environment and the health of the surrounding community. Based on the results of the study, the average B3 waste generation in Gayungan District was 2.33 g/person.day with a total B3 waste generation in Gayungan District of 85 kg/day, the types of B3 waste consisted of flammable, toxic and corrosive. Efforts that can be made to increase public knowledge about household B3 waste is to disseminate information on the introduction and control of household waste and how to manage household B3 waste independently. Based on the results of the community service activities carried out, it was found that there was an increase in community knowledge by 50% from the previous one based on the results of the pre-test and post-test conducted. Each of the question items that were asked to the community experienced an increase in each, when the activities were carried out the community was also very enthusiastic and eager to follow it, because previously this B3 waste socialization activity had never been carried out.Keywords: B3 Waste, B3 Waste Management